IMPLEMENTATION OF ISLAMIC BUSINESS ETHICS IN THE HOSPITALITY BUSINESS IN MANDAILING NATAL NORTH SUMATERA - Jureid (J-MABISYA, 2024)
Islamic business ethics is the application of the principles of Islamic values ??from the Koran and Hadith in business or commercial activities. Islamic business ethics is a very important factor in carrying out business processes or commercial activities based on Islamic law so that the business or commercial activity can be successful in the world with the blessing of Allah. Currently, Islamic business ethics are widely applied in various companies in carrying out their operations, one of which is hotel companies. This research aims to examine and analyze the application of Islamic business ethics in the hotel sector in Mandailing Natal, North Sumatra. This research uses a qualitative phenomenological method, while data collection uses observation and interviews. This research has produced the following specific findings: The values ??of Islamic business ethics that can be applied in business management, including hotel management, include: the value of monotheism, the value of justice, the value of free will, the value of responsibility, and the value of Ihsan. Meanwhile, the values ??of Islamic business ethics that have been implemented during the management of hotels in Mandailing Natal include the availability of prayer facilities and infrastructure equipped with several facilities, halal certification labels on the packaging of each food and beverage product provided by the hotel, providing rental fees to visitors based on facilities, selecting hotel guests or visitors, distributing promotional materials with writing or pictures that do not violate norms and ethics, shouting the call to prayer through loudspeakers to remind you of prayer times, paying attention to and responding to guests' complaints about the hotel, and always greeting hotel guests and other hotel staff very well. polite and friendly. This research concludes that Islamic business ethics have been applied to hotel companies in the Mandailing Natal area, North Sumatera.